2017
DOI: 10.3329/pa.v27i4.32131
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plant nutrient and weed management in direct wet seeded boro rice

Abstract: The experiment was conducted at the Farm of Farm Management Division, Bangladesh Agricultural University, Mymensingh during December 2012 to June 2013 to find out the effect of plant nutrient and weed management in direct wet seeded Boro rice. The experiment consisted of six nutrient management viz. Control (No manure-PM and N-P-K-S-Zn), PM at 5 t ha -1 , recommended dose of prilled urea (PU) and other inorganic fertilizers (i. e. 120, 60, 40, 10 and 5 kg of N, P 2 O 5 , K 2 O, S and ZnSO 4 , respectively), fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
3
2
0
Order By: Relevance
“…Among the different weed management practices the maximum straw yield (6.73 t ha -1 ) was obtained at pre-emergence herbicide (Panida 33 EC) @ 2.5 l ha -1 + hand weeding once at 20 DAS which was at par with hand weeding thrice at 20, 35 and 50 DAS (6.28 t ha -1 ) and the lowest (2.93 t ha -1 ) was obtained in weedy check (Table 2). Similar results were reported by Sarkar et al (2016) who noticed that application of pre-emergence herbicide (Panida 33 EC) @ 2.5 l ha -1 + hand weeding once at 20 DAS produced the highest straw yield compare to other treatments.…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…Among the different weed management practices the maximum straw yield (6.73 t ha -1 ) was obtained at pre-emergence herbicide (Panida 33 EC) @ 2.5 l ha -1 + hand weeding once at 20 DAS which was at par with hand weeding thrice at 20, 35 and 50 DAS (6.28 t ha -1 ) and the lowest (2.93 t ha -1 ) was obtained in weedy check (Table 2). Similar results were reported by Sarkar et al (2016) who noticed that application of pre-emergence herbicide (Panida 33 EC) @ 2.5 l ha -1 + hand weeding once at 20 DAS produced the highest straw yield compare to other treatments.…”
Section: Resultssupporting
confidence: 79%
“…This trend of grain yield was reported by Sarkar et al (2016) who reported that weed control by (Panida 33 EC) @ 2.5 l ha -1 + hand weeding once at 20 DAS increased grain yield. This might be due to the fact use of preemergence herbicide (Panida 33 EC) @ 2.5 l ha -1 + hand weeding once at 20 DAS in rice under aerobic culture reduced the weed competition and impaired growth and yield attributes resulting in higher grain yield.…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…Severe weed infestation reduces the grain yield by 70.80% in Aus rice, 30-40% for transplanted Aman rice and 22-36% for modern Boro rice cultivation in Bangladesh (Sarkar et al, 2017a). Zannat et al (2014) reported that grain yield reduced 28.16% due to weed infestation in aromatic rice Binadhan-9.The traditional method of weed control is hand weeding which is very much laborious and time consuming.…”
Section: Introductionmentioning
confidence: 99%